A case of Noonan's syndrome and hypoparathyroidism presenting with epilepsy. Issue 1 (January 1974) - Rudge, Peter; Neville, B. G. R.; Lascelles, P. T.
Abstract : A patient of 29 years is described with Noonan's syndrome and idiopathic hypoparathyroidism, who presented with epilepsy and myoclonus. Correction of the hypocalcaemia resulted in improvement of his myoclonus and psychiatric abnormalities. The embryological significance of the association is discussed.